Analysis of Production Cost Estimation to Increase Efficiency Using Activity Based Costing (ABC) Method in Indonesian Automotive Companies - Muhammad Afdhal Firdaus; Nadia Ayu Rahmanda; Fa'aizah Marsela Hedriyan (Ambidextrous Journal of Innovation Efficiency and Technology in Organization, 2026)
This study aims to analyze production cost estimation to improve efficiency in Indonesian Automotive Companies using the Activity Based Costing (ABC) method with a Systematic Literature Review (SLR) approach. The main problem in this study is the low accuracy of production cost estimation which causes waste and reduces operational efficiency. The research method was conducted by reviewing 20 relevant national and international journals for the period 2020–2025. The results show that the Activity Based Costing (ABC) method is able to improve the accuracy of cost estimation compared to traditional methods such as Full Costing because it allocates costs based on activities. The application of this method has been proven to reduce production costs by 15% and increase production efficiency from 70% to 90%. In addition, the use of technology such as Artificial Intelligence also has the potential to improve the accuracy of cost estimation. Thus, choosing the right cost estimation method has a significant impact on improving the company's operational efficiency